Strategi Pengembangan Industri Kreatif Berbasis Kearifan Lokal : (Studi Pada Sentra Industri Kerajinan Batik Banyuwangi) - Zaim Mukaffi; M. Nanang Choiruddin; Syahirul Alim (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2019)
The results of this study are 1) The value chain in the Banyuwangi batik craft industry is creation, production, distribution and commercialization. The four value chains are business processes that exist in the Banyuwangi batik craft industry. 2) The SWOT analysis technique shows the position index on internal factor analysis of + 0.796 and on the external position index of +0.8859. So that in the SWOT diagram that is seen in the position located on Quadrant I namely quadrant which means that the potential of the banyuwangi batik craft industry has a very large opportunity to grow and even compete with other batik industries. In addition, from the internal aspect shows that the ideas / ideas and creations that are built through the characteristics of Banyuwangi batik are very good. 3) To get optimal results in the development of creative industries in the Banyuwangi batik craft industry, collaboration between the main actors is needed with the starting points of these three main actors; (1) Commitment of intellectuals, business and government, continuous coordination between the three actors, and seek synergy to develop the creative industry. Where the role of the Banyuwangi district government has been to socialize about Banyuwangi batik to the outside public, both directly and through official media of the local government, besides training members, holding festivals both in Banyuwangi and outside. Whereas in terms of the role of academics, so far they have not contributed to the development of batik in Banyuwangi in the form of training, research results and community service. And from the aspect of the business actor, has carried out various methods with creative batik products according to their identity. The real form that is done is by using social media, opening cooperation with agents and opening their own outlets to introduce and sell their products.